ASINA Project: Towards a Methodological Data-Driven Sustainable and Safe-by-Design Approach for the Development of Nanomaterials - Furxhi, Irini; Perucca, Massimo; Blosi, Magda; Lopez de Ipiña, Jesús; Oliveira, Juliana; Murphy, Finbarr; Costa, Anna Luisa (Frontiers in Bioengineering and Biotechnology, 2022)
The novel chemical strategy for sustainability calls for a Sustainable and Safe-by-Design (SSbD) holistic approach to achieve protection of public health and the environment, industrial relevance, societal empowerment and regulatory preparedness. Based on it, ASINA project expands a data driven Management Methodology (ASINA-SMM) capturing quality, safety and sustainability criteria across the Nano-Enabled Products (NEPs) life-cycle. We base the development of this methodology through value chains of highly representative classes of NEPs in the market, namely self-cleaning/air purifying/antimicrobial coatings and ii) nano-structured capsules delivering active phases in cosmetics. These NEPs improve environmental quality and human health/wellness and have innovative competence to industrial sectors such as healthcare, textiles, cosmetics and medical devices. The purpose of this article is to visually exhibit and explain the ASINA approach, which allows identifying, combining and addressing the following pillars: environmental impact, techno-economic performance, functionality and human and environmental safety when developing novel NEPs, at an early stage. A metamodel supports the above by utilizing quality data collected throughout the NEPs’ lifecycle, for maximization of functionality (to meet stakeholders needs) and nano-safety (regulatory obligations) and for the minimization of costs (to meet business requirements) and environmental impacts (to achieve sustainability). Furthermore, ASINA explores digitalization opportunities (digital twins) to speed the nano-industry translation into automatic progress towards economic, social, environmental and governance sustainability.